2014
DOI: 10.3109/03014460.2014.977346
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Gilsanz-Ratib digital atlas and Greulich-Pyle atlas for bone age estimation in a Chinese sample

Abstract: Both atlases can be used on most age groups. However, the GR atlas is not recommended in boys aged 10-13 years, while the GP atlas is not suitable for girls aged 0-3 years. Therefore, the use of the GP or GR atlas is practical, depending on the age of the child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…There have been many studies worldwide that have compared different methods of BA estimation. [ 9 10 11 24 25 26 ] Studies using correlation coefficients (which only measure the strength of association and not an agreement between methods) done by Kim et al ,[ 9 ] Lin et al ,[ 11 ] and Kim et al [ 10 ] showed no differences between various BA methods. Similarly, in our study, the correlation between all three methods of BA estimation was very strong.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been many studies worldwide that have compared different methods of BA estimation. [ 9 10 11 24 25 26 ] Studies using correlation coefficients (which only measure the strength of association and not an agreement between methods) done by Kim et al ,[ 9 ] Lin et al ,[ 11 ] and Kim et al [ 10 ] showed no differences between various BA methods. Similarly, in our study, the correlation between all three methods of BA estimation was very strong.…”
Section: Discussionmentioning
confidence: 99%
“…To assess intrarater variation, the 30 radiographs were analyzed initially and then were reevaluated by the same four observers independently by the three methods after a 4-week interval. [ 11 ] If there were statistically significant inter-rater (disagreement among the four observers) and intra-rater differences, they were checked for clinical significance. If the differences were within the range of SDs given in each of the methods of BA assessment, it was considered as clinically not significant and if they were out of range, it was considered as clinically significant.…”
Section: Ethodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The Greulich and Pyle (GP) radiographic atlas of the hand and wrist is one of the oldest and most commonly utilized atlas for this purpose worldwide [4, 5]. Gilsanz and Ratibin (GR) atlas also provides a bone age assessment scheme using detailed images of ossification centres in hand radiographs of healthy children and shows comparable accuracy to GP method [6]. Other methods such as Girdany and Golden (GG) method utilize a plain radiograph of various large joints of the body and determine skeletal age based upon the appearance of ossification centres around those joints [7].…”
Section: Introductionmentioning
confidence: 99%
“…An additional potential limitation of G&P is its applicability to modern diverse populations since it is based upon a study of a more focused patient population in the 1930s [6]. More recently, alternative atlases to G&P also containing left hand radiographic standards have been developed [8–10]; however, there is overall a relative paucity of peer-reviewed data available on the clinical utility or accuracy of such alternatives [11, 12]. No previous study has compared the most recent of these alternative atlases— Skeletal Development of the Hand and Wrist: Digital Bone Age Companion (DBAC) (Oxford University Press, New York)—to G&P. DBAC [8] is a commercially available software application that accompanies a hardcopy bone age reference textbook based upon G&P. The precursors of the DBAC standards came from candidate clinical digital bone age images while referencing the G&P maturity indicators.…”
Section: Introductionmentioning
confidence: 99%